Ontogenetic changes in leaf phenology of a canopy species, Elateriospermum tapos (Ephorbiaceae), in a Malaysian rain forest - Osada, Noriyuki; Takeda, Hiroshi; Furukawa, Akio; Awang, Muhamad (Cambridge University Press, 2002)
Leaf phenology was studied in individuals of a canopy species, Elateriospermum tapos (Euphorbiaceae), at various ontogenetic stages, in a Malaysian rain forest. The timing of leaf emergence was not synchronized among sapling individuals, and was not correlated with any meteorological factors of the preceding month. The timing of leaf fall in saplings was positively correlated with net radiation, and maximum and minimum temperature, but negatively correlated with relative humidity the preceding month, although these correlations were weak. The leaf production rate was larger under higher light, but the leaf fall rate was not related to the light regime of the saplings. Thus, leaf production was enhanced by the light availability for each individual, while leaf fall may have been enhanced by drought stress. Non-synchronous leaf production appears to be important for sapling growth, allowing saplings to occupy better-lit space quickly. On the other hand, tall trees showed a clear synchronous leaf-fall pattern, with an annual cycle, and no meteorological factors were correlated with the timing of leaf fall. Mature trees of this species produced flowers simultaneously with new leaves, after shedding their leaves. This suggests that the need to synchronize flowering might be the primary determinant of leaf production phenology in mature individuals.